Pengarusutamaan Islam Moderat Melalui Penafsiran Al-Qur’an di Media Sosial Indonesia - Ulya Fikriyati (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2022)
There is a growing recognition among certain individuals of the significance of integrating moderate Islam into the mainstream via diverse social media platforms. This article examines the methodologies employed by two prominent Indonesian social media platforms in February 2021, which consistently promote moderate Islam by interpreting Qur'anic verses. Communication technique theory is utilised to analyse the data derived from the uploads of each sample account from the moment the account was created until July 2021. The analysis provides two explanations.Firstly, the tafsiralquran.id account was founded by a group of students from UIN Sunan Ampel, UIN Sunan Kalijaga, and UIN Syarif Hidayatullah. Secondly, the quranreview account, which is led by students from Gadjah Mada University, employs two distinct approaches to mainstreaming moderate Islam. Thirdly, both accounts utilise informative-persuasive communication techniques, of which only five are present out of the six that are considered. By means of repeated insertion of key values and repetition of each account's motto and slogan, pervasive techniques are implemented. The tafsiralquran.id account seldom employs instructive techniques; in contrast, the QuranReview account makes extensive use of them via slang. Different models of human relations techniques are utilised in both accounts.